YOGA SEBAGAI ALTERNATIF PENINGKATAN SIKAP SPIRITUAL - Made Adi Nugraha Tristaningrat Komang Trisna Mahartini Novi Kusuma Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This Literature Study is intended to be learned which is carried out from yoga activities towards increasing spiritual attitude. Yoga is not only limited to physical training, but yoga is also rich in exercises for the mind and soul, yoga is a method for achieving harmony in body, mind, soul, thus happiness is perfectly accessible to the noble lights that are needed spiritually. Yoga is done to make the body healthy and uplifting so there is no laziness in carrying out positive activities such as prayer which of course enhances the spirit of becoming a better person. There is satisfaction in spiritual matters, there are also other considerations to be gained, for example when pranayama can facilitate breathing and solar movements namasakar means worshiping the Solar God through asanas movements helps make it flexible and flexible and the most popular thing seen by yoga movements that are obtained spiritually, in addition to making movements there are also spells in them that make it more manageable and increase calm in the soul.